Comparison of Hepatic 2D Sandwich Cultures and 3D Spheroids for Long-term Toxicity Applications: A Multicenter Study. (10th January 2018) - Bell, Catherine C; Dankers, Anita C A; Lauschke, Volker M; Sison-Young, Rowena; Jenkins, Roz; Rowe, Cliff; Goldring, Chris E; Park, Kevin; Regan, Sophie L; Walker, Tracy; Schofield, Chris; Baze, Audrey; et al.
Abstract: Primary human hepatocytes (PHHs) are commonly used for in vitro studies of drug-induced liver injury. However, when cultured as 2D monolayers, PHH lose crucial hepatic functions within hours. This dedifferentiation can be ameliorated when PHHs are cultured in sandwich configuration (2Dsw), particularly when cultures are regularly re-overlaid with extracellular matrix, or as 3D spheroids. In this study, the 6 participating laboratories evaluated the robustness of these 2 model systems made from cryopreserved PHH from the same donors considering both inter-donor and inter-laboratory variability and compared their suitability for use in repeated-dose toxicity studies using 5 different hepatotoxins with different toxicity mechanisms. We found that expression levels of proteins involved in drug absorption, distribution, metabolism, and excretion, as well as catalytic activities of 5 different CYPs, were significantly higher in 3D spheroid cultures, potentially affecting the exposure of the cells to drugs and their metabolites. Furthermore, global proteomic analyses revealed that PHH in 3D spheroid configuration were temporally stable whereas proteomes from the same donors in 2Dsw cultures showed substantial alterations in protein expression patterns over the 14 days in culture. Overall, spheroid cultures were more sensitive to the hepatotoxic compounds investigated, particularly upon long-term exposures, across testing sites with little inter-laboratory or inter-donor variability. The data presented here suggest that repeated-dosing regimens improve the predictivity of in vitro toxicity assays, and that PHH spheroids provide a sensitive and robust system for long-term mechanistic studies of drug-induced hepatotoxicity, whereas the 2Dsw system has a more dedifferentiated phenotype and lower sensitivity to detect hepatotoxicity.